2011
DOI: 10.1002/chem.201002318
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoinduced Energy‐ and Electron‐Transfer Processes of C60–Oligothienylenevinylene–C70 Dumbbell Compounds

Abstract: Unsymmetric dumbbell molecules based on N-methylpyrrolidine[60]fullerene, oligothienylenevinylenes (nTV; n=2, 4), and N-methylpyrrolidine[70]fullerene, namely, C(60) -nTV-C(70) were synthesized and their photophysical properties were studied. In nonpolar solvents, photoinduced energy-transfer process predominantly takes place from the singlet excited state of nTV to C(60) and C(70) , as was confirmed by time-resolved emission and transient absorption spectroscopy. In polar solvent, charge-separation processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…Based on this pattern, the chemical shift of the signals and by comparison to the previously reported 1 H NMR spectrum of compound B (Fig. 2a, cis-2 H endo-H endo) [24,29,32], we suggest that compounds 1 and 2 exhibit the same endoeendo conformation. UV/vis spectroscopy is a useful tool to assign fullerene isomers since unique absorption patterns are observed for each derivative based on the addition sites and not on the nature of the addends.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Based on this pattern, the chemical shift of the signals and by comparison to the previously reported 1 H NMR spectrum of compound B (Fig. 2a, cis-2 H endo-H endo) [24,29,32], we suggest that compounds 1 and 2 exhibit the same endoeendo conformation. UV/vis spectroscopy is a useful tool to assign fullerene isomers since unique absorption patterns are observed for each derivative based on the addition sites and not on the nature of the addends.…”
Section: Resultssupporting
confidence: 74%
“…showed similar UV/vis absorption spectra to that reported for the a-1-b and a-1-a regioisomers [32], respectively (see ESI) [31].…”
Section: Structural Characterization Of Unsymmetric Bis-pyrrolidines supporting
confidence: 76%
“…Other techniques such as HPLC can further confirm the isomeric nature of these mixtures. For instance, Urbani et al [37] have prepared C70-fuleropyrrodines with a similar approach here described and confirmed the presence of two kinds of isomeric products, namely, α and the β-types. However, differentiation within the α isomers or the β isomers was not possible.…”
Section: Resultsmentioning
confidence: 77%
“…We observed that the solubility of the resulting C 70 derivatives was greatly improved when compared with the solubility of the C 60 derivatives: while derivatives 70a-70d [37] were soluble in dichloromethane, derivatives 60a-60d were far less soluble, and only solvents such as toluene and CS 2 could dissolve them. The final products were separated from the unreacted starting material (C 60 or C 70 ) and other by-products by silica gel chromatography using a mixture of toluene/hexane.…”
Section: Resultsmentioning
confidence: 94%
“…p-Conjugated oligomers as oligothiophene (OT) [5] and oligophenylenevinylene (OPV) [6] moieties have been shown to act as long distance molecular wires in the efficient photoinduced electron transfer from the porphyrin chromophore to the fullerene. Recently, we have described the use of oligothienylenevinylene oligomers (nTVs) [7], where the thiophene moieties was substituted by alkyl chains, as efficient bridges in donor-donor [8], acceptoracceptor [9] or donor-acceptor [10] systems showing an attenuation factor for electron transfer as low as 0.016 Å -1 [11]. The functionalization of thiophenes with ethylenedioxy groups produced the well known 3,4-ethylenedioxythiophene (EDOT).…”
Section: Introductionmentioning
confidence: 99%